La astronomía en textos escolares de educación primaria - García Barros, Susana; Martínez Losada, Cristina; Mondelo Alonso, Matilde; Vega Marcote, Pedro (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
In this paper we analyse the way in which the study of Astronomy is dealt with in Primary School textbooks. Moreover, we study how the topic should be approached at this school level.